Sellar and Parasellar Metastatic Tumors - Altay, Tamer (Hindawi Publishing Corporation, 2012)
The sellar and parasellar (SPS) region is a complex area rich in vital neurovascular structures and as such may be the location of first manifestation of a systemic malignancy. Metastases to this region are rare; breast cancer is the most common source among those that metastasize to the SPS region. Ophthalmoplegia, headache, retroorbital or facial pain, diabetes insipidus, and visual field defects are the most commonly reported symptoms. Lack of specific clinical and radiological features renders SPS metastases difficult to differentiate from the other frequently encountered lesions in this area, especially when there is no known history of a primary disease. Currently accepted management is multimodality therapy that includes biopsy and/or palliative surgical resection, radiation, and chemotherapy. Although no significant survival benefits have been shown by the surgical series, surgical resection may improve quality of life. Here we review the relevant literature and present six illustrative cases from our own institution.